Tropical freshwater ecosystems have lower bacterial growth efficiency than temperate ones - Amado, André M.; Meirelles-Pereira, Frederico; Vidal, Luciana D.; Sarmento, Hugo; Suhett, Albert; Farjalla, Vinicius F.; Cotner, James; Roland, Fabio (Frontiers in Microbiology, 2013)
Current models and observations indicate that bacterial respiration should increase and growth efficiency (BGE) should decrease with increasing temperatures. However, these models and observations are mostly derived from data collected primarily in temperate regions, and the tropics are under-represented. The aim of this work was to compare bacterial metabolism, namely bacterial production (BP) and respiration (BR), bacterial growth efficiency (BGE) and bacterial carbon demand (BCD) between tropical and temperate ecosystems via a literature review and using unpublished data. We hypothesized that (i) tropical ecosystems have higher metabolism than temperate ones and, (ii) that BGE is lower in tropical relative to temperate ecosystems. We collected a total of 498 coupled BP and BR observations (Ntotal = 498; Ntemperate = 301; Ntropical = 197), calculated BGE (BP/(BP+BR)) and BCD (BP+BR) for each case and examined patterns using a model II regression analysis and compared each parameter between the two regions using non parametric Mann–Whitney U test. We observed a significant positive linear regression between BR and BP for the whole dataset, and also for tropical and temperate data separately. We found that BP, BR and BCD were higher in the tropics, but BGE was lower compared to temperate regions. Also, BR rates per BP unit are at least two fold higher in the tropics than in temperate ecosystems. We argue that higher temperature, nutrient limitation, and light exposure all contribute to lower BGE in the tropics, mediated through effects on thermodynamics, substrate stoichiometry, nutrient availability and interactions with photochemically produced compounds. More efforts are needed in this study topic in the tropics, but our work indicates that bottom-up (nutrient availability and resource stoichiometry) and top-down (grazer pressure) processes, coupled with thermodynamic constraints, might contribute to the lower BGE in the tropics relative to temperate regions.